Urgensi Kritik atas Pasal Pidana Lingkungan dan Pertanggungjawaban Korporasi serta Pengurus Korporasi dalam KUHP - Kifli, Susiana (UNES Law Review, 2023)
Indonesia, as a developing country, still needs a lot of development in all sectors, especially in the economic sector. The role of corporations in the economic development of society not only has a positive impact, but also has negative impacts, one of which is the development of deviant behavior carried out by corporations with economic motives whose characteristics and modus operandi are different from conventional crimes in general so that law enforcement requires handling with special instruments. . The research method used is normative legal research. The urgency of criminal liability for corporations as perpetrators of environmental criminal acts is because corporate criminal acts in the environmental sector have widespread and complex negative impacts so that they not only cause direct losses to society and the environment but also disrupt the financial and economic stability of the country, considering the actions Environmental crimes are carried out with economic motives. The punishment pattern for corporations that commit environmental crimes in the PPLH Law should contain provisions related to environmental conservation-based punishment patterns which include the severity of criminal fines, regulations for the implementation of criminal fines, and sanctions for remedial action resulting from criminal acts.